Biomechanical differences in experts' and novices' footstep patterns during a palletizing task. (January 2023) - Marcotte, Jasmin Vallée; Robert-Lachaine, Xavier; Denis, Denys; Muller, Antoine; Plamondon, André; Corbeil, Philippe
Abstract: Very few studies have examined differences between experts' and novices' foot positioning and movements during manual materials handling tasks. The impact of footstep patterns on low back loading needs to be better understood. The goals of this study were to characterize foot placement and movements in novices and experts and to assess their impact on back loading considering the height of grasp. The task consisted in transferring 24 15 kg boxes from a pallet to another. Foot placement and movements were classified with a recently developed taxonomy. Results show that experts' feet remained static more often than novices' feet during the lifting phase. Positioning the feet towards the deposit site during lifting increased asymmetrical moments, especially for novices. Positioning one foot forward increased asymmetrical moments for novices. Overall, footstep strategies are an effective indicator of low back exposure and should be considered in ergonomic studies. Highlights: Experts' feet remain static more often than novices' feet during lifting. Novices show more variable foot movements than experts. Sagittal and asymmetrical moments are influenced by footstep strategy.